Understanding identity salience and English as a Foreign Language teaching practices: A case study of multi‐subject generalist teachers - Alam, Md. Saiful; Asmawi, Adelina (Review of education (Oxford), 2023)
The scarcity of teachers worldwide has led to educators teaching multiple subjects outside their area of expertise. This challenge of teaching out‐of‐field or multi‐subject instruction raises the need for (re)constructing the identity of multi‐subject generalist teachers (M‐SGTs). However, the matter has received little attention in current literature. This study aimed to explore the process by which M‐SGTs develop a salient identity as EFL teachers and how this identity impacts their practices in teaching EFL. To achieve this, a case‐study approach was employed, and six M‐SGTs from three private kindergarten schools in rural Bangladesh were selected using convenient sampling. Data were gathered from observation protocols, semi‐structured interviews, and documents. The interviews and observation protocols were transcribed and coded, while the documents were reviewed thematically and categorically in line with Kvale's recommendations. The results of this investigation highlight the complex and multifaceted nature of the development of salient identity as EFL teachers among M‐SGTs. The study reveals that M‐SGTs develop a strong identity as EFL teachers through negotiation, adaptation, subject selection, confidence, language acquisition experience, pre‐service pedagogical skills, social support, positive feedback and endorsement by principals. The study also finds that M‐SGTs' salient identity is reflected in their teaching practices that involve being role models, adapting English language instruction, employing interactivity, differentiation in pedagogy, comprehensive feedback, whole‐class teaching and the use of supplementary materials. This paper ends with an important implication.